(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Brucellosis occurs in all age groups, including children. In children, brucellosis typically presents more benignly. In most cases during the acute phase of the disease, functional disturbances of the central nervous system are observed, with children complaining of headaches and poor sleep. Parents note their rapid fatigue, poor mood, unexplained irritability, and tearfulness. Signs of autonomic nervous system involvement during the acute phase include labile heart rate, tendency to lower blood pressure, acrocyanosis, and skin pigmentation changes.